Concept and Implementation of Business Model Canvas in Startup Companies: Relationship with Customers, Customers Segments and Market Trends - Nunung Ayu Sofiati; Christimulia Purnama Trimurti; Rintis Eko Widodo; Fitria Ariyani; Cecep Pahrudin (Dinasti International Journal of Digital Business Management, 2024)
The purpose of this literature research is expected to build a hypothesis regarding the influence between variables that can later be used for further research in the scope of marketing management. The research article literature review concept and application of canvas business model in startup companies: customer relationships, customer segments and market trends is a scientific literature article in the scope of marketing management science. The approach used in this literature review research is descriptive qualitative. The data collection technique is to use literature studies or conduct a review of relevant previous articles. The data used in this descriptive qualitative approach comes from previous research that is relevant to this research and is sourced from academic online media such as Thomson Reuters Journal, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Web of Science, Sinta Journal, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Customer Relationships affect the Canvas Business Model Concept in Startup Companies; 2) Customer Segments affect the Canvas Business Model Concept in Startup Companies; 3) Market Trends affect the Canvas Business Model Concept in Startup Companies; 4) Customer Relationships Influence the Implementation of the Canvas Business Model in Startup Companies; 5) Customer Segments Influence the Implementation of the Canvas Business Model in Startup Companies; and 6) Market Trends Influence the Implementation of the Canvas Business